Liveability of Kathmandu’s Traditional Neighbourhood: A Case of Te Bahal - Tuladhar, Yaju; Pradhan Salike, Inu (Advances in Engineering and Technology: An International Journal, 2026)
The study investigates neighbourhood liveability and its contextual factors in case of Kathmandu’s traditional neighbourhood of Te bahal. A mixed-methods approach was applied in two phases. First phase involved thematic analysis of qualitative interviews and pattern matching was conducted in NVivo to identify contextually relevant themes. The main theme was identified as problem of accessibility and mobility in open bahal space. Access to open space, walkability, and parking pressure were found to be affecting factors to accessibility. In second phase, quantitative survey was conducted in four point Likert scale and administered using KoboToolbox to assess the perceived importance and satisfaction of factors affecting the main theme. Data was processed in SPSS and analysed using mean scores, and gap analysis. Internal reliability was tested with Cronbach’s alpha. Findings indicated that residents valued walkability, (absence of) parking pressure, and access to open spaces as mostly important for liveability of Te bahal. Mean satisfaction ratings were lower than mean importance ratings, so all factors showed positive gap. Particularly, the satisfaction response had large standard deviation. The study speculates trade-offs between different liveability factors by residents and recommends possible exploration of liveability factors that carry different weights among a larger and diverse population size.